Diagnóstico radiológico de agenesia de terceros molares en escolares y adolescentes. Riobamba, 2018 - Huilcarema Borja, Francis Coralia (2019)
Considering that third molars are the teeth with greater variability in both number and shape and size; they are responsible for odontalgias, surgical difficulties during exodontics and post-surgical complications, including agenesis. It is an important issue because it varies considerably depending on the population studied. This research aimed to determine the agenesis of the third molars in the population of the dental clinic C.O.I. and specifically determine dental agenesis according to gender and maxilla. The method was descriptive, observational and cross-sectional, examining 60 panoramic radiographs taken from the dental center C.O.I of Riobamba. The results obtained showed 60% agenesis of moral third parties of the entire sample studied, pieces # 1.8 and # 2.8 were the ones with the highest prevalence of agenesis. In addition, in terms of gender, the male presented 21% agenesis and 15% corresponding to the female sex. It was determined that there was no significant statistical difference between dental agenesis and sex.